(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Isolated Carpometacarpal (CMC) joints dislocations is an extremely uncommon injury. It is often missed in polytrauma patient. It can be associated with ulnar nerve damage and detailed neurologic assessment is often warranted to avoid long term deficit. Early closed reduction usually leads to a good outcome. This case report describes an uncommon dorsal dislocation of the fifth Carpometacarpal joint in 33-year-old man. It was reduced under local anesthesia and stabilized in an ulnar gutter splint. Post-reduction radiographs revealed satisfactory reduction and alignment. At 4 weeks and subsequent follow-up reduction was stable without sensory loss and gradually regaining good range of motion till last follow-up at 6 months.